Internalisasi Nilai-Nilai Sila Ke Dua Pancasila Sebagai Upaya Pencegahan Aksi Perundungan di Lingkungan Pendidikan (Studi Kasus di SMAN 12 Bandung) - Saputra, Kiki Hananda; Normansyah, Asep Deni; Khoerudin, Cep miftah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Internalization of the Values of the Second Principle of Pancasila as an Effort to Prevent Bullying in the Educational Environment (Case Study at Senior High School 12 Bandung). This research aims to examine the internalization of the second principle of Pancasila as an effort to prevent bullying in educational environments, with a case study at SMAN 12 Bandung. Bullying in schools is a serious issue that can affect the well-being of students and disrupt the teaching and learning process. Therefore, a comprehensive approach is needed to address this problem. The research uses a case study method with a qualitative approach. Data were obtained through interviews, observations, and document analysis. Data analysis was conducted using qualitative descriptive methods to understand the process and outcomes. The research results indicate that the internalization of the values of just and civilized humanity at SMAN 12 Bandung is carried out through various programs and activities. Character education programs, teacher training, extracurricular activities, and anti-bullying awareness campaigns have successfully enhanced students’ understanding and positive attitudes towards human values. Additionally, counseling services and an effective reporting system also support bullying prevention efforts in this school. This study concludes that the internalization of the second principle of Pancasila is effective in preventing bullying in educational settings. The implementation of these values creates a safer, fairer, and more civilized school environment. The study recommends that the school continue to strengthen character education programs, enhance cooperation with parents and the community, conduct comparative studies, and develop more innovative teaching methods.